The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/jkm-11-2018-0687
|View full text |Cite
|
Sign up to set email alerts
|

Top-down knowledge hiding and innovative work behavior (IWB): a three-way moderated-mediation analysis of self-efficacy and local/foreign status

Abstract: Purpose This paper aims to examine the consequences for innovative work behavior (IWB) of top-down knowledge hiding – that is, supervisors’ knowledge hiding from supervisees (SKHS). Drawing on social learning theory, the authors test the three-way moderated-mediation model in which the direct effect of SKHS on IWB is first mediated by self-efficacy and then further moderated by supervisor and supervisee nationality (locals versus foreigners). Design/methodology/approach The authors collected multi-sourced da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
136
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(144 citation statements)
references
References 86 publications
(197 reference statements)
5
136
0
3
Order By: Relevance
“…So far, to the best of our knowledge, only two empirical studies (i.e. Arain et al, 2018, 2019) have focused on KHSS and its detrimental consequences on subordinates’ self‐efficacy, supervisor directed trust, innovative work behavior, and supervisor directed organizational citizenship behavior (SOCB). Subsequently, more research on the consequences of KHSS is warranted for at least two reasons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, to the best of our knowledge, only two empirical studies (i.e. Arain et al, 2018, 2019) have focused on KHSS and its detrimental consequences on subordinates’ self‐efficacy, supervisor directed trust, innovative work behavior, and supervisor directed organizational citizenship behavior (SOCB). Subsequently, more research on the consequences of KHSS is warranted for at least two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…First, studies focusing on the consequences of KHSS (i.e. Arain et al, 2018, 2019) have suggested that reducing positive work attitudes and behaviors are the most likely manifestations of subordinates’ response to KHSS. Taking a step further, we suggest that subordinates may respond to KHSS by not only decreasing these positive work attitudes and behaviors but also by increasing their counterproductive behavior, such as SS.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge hiding has gained prominent attention in the past few years. Plenty of recent studies have either tried to identify the consequences as well as the potential antecedents of knowledge hiding either between coworkers or in a top‐down management context (Butt and Ahmad, 2019; Butt, 2019a,b,c; Connelley et al, 2019; Cheng et al, 2008; Samuel et al, 2011; Fang, 2017; Rashed et al 2010; Shih et al, 2012: Arain et al, 2018; Arain et al, 2019). Connelly et al (2012, p. 65) define knowledge hiding as “an intentional attempt by an individual to withhold or conceal knowledge that has been requested by another person.” Extant literature on the potential antecedents of knowledge hiding in a business discipline argues that managers hide knowledge for various reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Specialists usually have knowledge resources, the circulation of which is limited due to its specificity (stickiness, ambiguity), or the attitudes of the intellectual workers themselves. They often believe that knowledge sharing is unnatural (Arain et al, 2019), or that knowledge is the source of individual notions of power in an organization (Butler, 2016). In their case, interpersonal relationships and personal contacts that create the context of trust and reciprocity are the most important (Ensign and Hébert, 2010;Anand et al, 2019).…”
Section: Determinants Of the Diffusion Of Specialist Knowledgementioning
confidence: 99%
“…Being "deep-smarts" (Sumbal et al, 2020), most knowledge workers consider knowledge as power and may not be willing to share their knowledge entirely (Jayasingam et al, 2016). They adopt attitudes that restrain the flow of knowledge, even deliberately concealing it (Arain et al, 2019), considering their knowledge too valuable (Afshar Jalili and Ghaleh, 2020) for free diffusion. This is especially true with tacit knowledge (Holste and Fields, 2010).…”
Section: Introductionmentioning
confidence: 99%